Talvipäivä Hangossa - Lauri Törhönen; Esa Vuorinen; Johan Hake; Tuula Mehtonen; Petri Mäkinen; Tom Forsström; Stiina Laakso; Jörn Donner (1988)
Kamera kävi Hangossa katsomassa, mitä kaupungissa tapahtuu talvisena lauantaipäivänä.
Keywords: kaupungit; Hanko